Courtship, copulation, and territorialistic behaviors of Tropidurus torquatus (Tropiduridae) in a fragment of Cerrado in Central-West Brazil - SILVA, Débora Neves; CASSEL, Monica; FERREIRA, Adelina; MEHANNA, Mahmoud (Revista Ambientale, 2022)
This study observed and recorded courtship, copulation, and territorialistic behaviors in Tropidurus torquatus. Males of this species used a head bobbing or “push-up” display, which is the main communication sign with other males. Females, in turn, performed tail lifting, a specific sexual stimulus behavior indicating acceptance of copulation. Courtship took place with coordinated movements for both males and females and could result in effective copulation; females seemed to prefer dominant males during the reproductive period. Territorialistic behaviors occurred before and after courtship, demonstrating the efforts made by dominant males of T. torquatus to maintain their territory during the reproductive season.